2013
DOI: 10.1371/journal.pone.0058095
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia Gravis: Analysis of Serum Autoantibody Reactivities to 1827 Potential Human Autoantigens by Protein Macroarrays

Abstract: BackgroundMyasthenia gravis is a disorder of neuromuscular transmission associated with autoantibodies against the nicotinic acetylcholine receptor. We have previously developed a customized protein macroarray comprising 1827 potential human autoantigens, which permitted to discriminate sera of patients with different cancers from sera of healthy controls, but has not yet been evaluated in antibody-mediated autoimmune diseases.ObjectiveTo determine whether autoantibody signatures obtained by protein macroarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Poly(A)-binding proteins bind the poly(A) tail of messenger RNAs and control mRNA stability and translation initiation. Although PABPC3 has not yet been reported as an autoAg, its paralog PABPC1 has been found to be an autoAg [25].…”
Section: Resultsmentioning
confidence: 99%
“…Poly(A)-binding proteins bind the poly(A) tail of messenger RNAs and control mRNA stability and translation initiation. Although PABPC3 has not yet been reported as an autoAg, its paralog PABPC1 has been found to be an autoAg [25].…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated the common features of the identified protein antigens of the tumor-specific dominant B cell clones. Knowledge-based exploration of the biological and clinical features of the protein antigens revealed that almost all the humoral protein antigens we discovered in tumor environments have also been reported as immunological targets of humoral autoimmunity in multiple autoimmune diseases such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), myasthenia gravis (MG), multiple sclerosis (MS), primary biliary cirrhosis (PBC), and Sjogren's syndrome (SS) [11][12][13][14][15][16][17][18][19][20][21][22] (Table 1). This shared feature of humoral immunity in tumors and autoimmunity in view of their target protein antigens suggested that these two clinically important aspects of immunological dysregulations are attributable to common molecular mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Potential cross-reactivity of auto-antibodies to fibrinogen may protect fibrinogen from activation, but this seems unlikely as it appears to occur with all serotypes. Interestingly, a previous proteome-wide screening for cross-reactivity of autoantibodies in MG patients failed to report fibrinogen as a potential target 38 . Nonetheless, other factors may bind fibrinogen and preclude its conversion to fibrin.…”
Section: Discussionmentioning
confidence: 99%